The partner as a caregiver in the birth process - Camila Fernandes da Silva Carvalho; Isaiane da Silva Carvalho; Rosineide Santana de Brito; Allyne Fortes Vitor; Ana Luísa Brandão de Carvalho Lira (Rev Rene)
Objective: to analyze the scientific production about the role of the man as a caregiver during the birth process of his partner. Methods: integrative review held in electronic databases Scopus, Cumulative Index to Nursing and Allied Health Literature, PubMed, ISI Web of Knowledge, and Latin American and Caribbean in Health Sciences. Results: there were 389 scientific articles located, of which 26 studies were selected that showed active roles - physical and emotional support - and passive roles – spectator or total lack of viewer participation – of the partner during the birth process. The monitoring of this event by the father is considered positive experience. However, the lack of incentive limits their active participation. Conclusion: despite the historical, religious, cultural, institutional or individual barriers, there is a desire to actively participating in the child´s birth, even though sometimes parents are unprepared to provide the support they would like.